2018
DOI: 10.1186/s12913-018-3201-z
|View full text |Cite
|
Sign up to set email alerts
|

“They can rest at home”: an observational study of patients’ quality of sleep in an Australian hospital

Abstract: BackgroundPoor sleep is known to adversely affect hospital patients’ recovery and rehabilitation. The aim of the study was to investigate the perceived duration and quality of patient sleep and identify any environmental factors associated with patient-reported poor sleep in hospital.MethodA cross-sectional study was conducted involving 15 clinical units within a 672-bed tertiary-referral hospital in Australia. Semi-structured interviews to determine perceptions of sleep quantity and quality and factors that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
77
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 41 publications
5
77
1
2
Order By: Relevance
“…Furthermore, this study result showed that room temperature did not affect sleep quality (p-value of 0.455 (> 0.05). The results of this study are in line with research (Delaney, Currie, Huang, Lopez, & Van Haren, 2018), which states that environmental factors (room temperature) are not significantly related to patient sleep quality.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, this study result showed that room temperature did not affect sleep quality (p-value of 0.455 (> 0.05). The results of this study are in line with research (Delaney, Currie, Huang, Lopez, & Van Haren, 2018), which states that environmental factors (room temperature) are not significantly related to patient sleep quality.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, other previous studies (Delaney et al, 2018;Ding et al, 2017) reported that there is a relationship between noise and poor sleep quality. Moreover, Delaney et al, (2018) found that clinical care affected patients' sleep (34.3%), while environmental noise made 32.1% disturbance towards patients' sleep quality. Patients reported that they found it very difficult to stay sleep in the hospital.…”
Section: Discussionmentioning
confidence: 87%
“…It is, therefore, unsurprising that observational studies on ICUs identify these as major disruptive noise sources. Nearly 80% of disruptive noises are generated by monitor or ventilator alarms and speech . However, a significant proportion of the noise coming from speech is not required for patient care , and almost 90% of alarms from physiological monitors are ‘false positives’, with no patient benefit .…”
Section: Discussionmentioning
confidence: 99%
“…VS assessments are the second most common cause of sleep disruption in the hospitalized patient 16 , and safely reducing these interventions overnight can improve patient sleep quality and quantity while leading to better health outcomes. Multiple studies have measured the quality and quantity of sleep in hospitalized patients around the world, showing significant reductions in sleep quality for patients in North America 1,2,7 , Europe 17 , and Australia 18 , among others. This sleep quality reduction has been linked to a range of adverse health outcomes, including delirium; cardiac and metabolic derangements; cognitive impairment, especially in older adults 4,19 ; development of various pain conditions; elevation of inflammatory markers; a decline in self-reported physical health-status 20 ; weakened immunity; hypertension; elevated stress hormones; and increased mortality 3 .…”
Section: Discussionmentioning
confidence: 99%